2020
DOI: 10.4491/eer.2019.521
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of physicochemical characteristics and associated metal contamination risk in the Narmada River, India

Abstract: River Narmada is the fifth largest holy river of Madhya Pradesh (M.P) flowing in the central part of India. The river receives large quantity of untreated/partially treated wastewater enriched with heavy metals and supplementary toxic organic pollutants. This study aims to assess the water quality status in river Narmada using indices like comprehensive pollution index (CPI), heavy metal pollution index (HPI), risk assessment index (RAI) and cancer risk index (CRI), for human use. The presence of faecal colifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The parameters loading in PC1 governed the nutrient input source from natural sources, while positive loading of parameters in PC2 defined the nutrient input through direct discharge of partially or untreated treated domestic or industrial wastewater into the river ( Mishra and Kumar, 2020 , Kumar et al, 2018 ). During the comparative analysis of parameters loading in PCs at all locations, it was noted that the parameter K, SO 4 , Na, and Cl were positively loaded in PC1, which signified the input of their salts from both natural source through runoff or landslides and anthropogenic agricultural activities (where use of chemical herbicides, fertilizers, pesticides, and mining operations occurs) ( Dalakoti et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The parameters loading in PC1 governed the nutrient input source from natural sources, while positive loading of parameters in PC2 defined the nutrient input through direct discharge of partially or untreated treated domestic or industrial wastewater into the river ( Mishra and Kumar, 2020 , Kumar et al, 2018 ). During the comparative analysis of parameters loading in PCs at all locations, it was noted that the parameter K, SO 4 , Na, and Cl were positively loaded in PC1, which signified the input of their salts from both natural source through runoff or landslides and anthropogenic agricultural activities (where use of chemical herbicides, fertilizers, pesticides, and mining operations occurs) ( Dalakoti et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, various water quality indices have been developed for monitoring surface water quality of rivers such as the Weighted Arithmetic Water Quality Index, National Sanitation Foundation Water Quality Index, Comprehensive Pollution Index, Carlson's trophic index, and Canadian Council of Ministers of the Environment Water Quality Index (Batabyal & Chakraborty, 2015;Gupta et al, 2017;Kumar, Sharma, & Rai, 2017;Mishra & Kumar, 2020;Mishra, Kumar, & Shukla, 2016).…”
Section: Water Quality Index (Wqi)mentioning
confidence: 99%
“…Several studies have been carried on different aspects of water quality in the river, including those by (Mishra & Kumar, 2020;Gupta, Pandey, & Hussain, 2017;Sharma, Dixit, Jain, Shah, & Vishwakarma, 2008;Sharma, Bora, & Shukla, 2013;Soni et al, 2013;Zingde, Chander, Rokade, & Desai, 1981). These are all based on specific locations, and dealt with relatively few parameters and particular seasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, high lead concentrations in groundwater pose significant risks to consumers. Indeed, in most research [36,46,56], it is indicated that increased blood Pb concentration affects behaviour, cognitive performance, postnatal growth, delays puberty and reduces the hearing ability of infants and children. In adults, Pb causes cardiovascular, central nervous system, kidney, fertility, and cancer problems.…”
Section: Seasonal Distribution Of Chemical and Bacteriological Qualitmentioning
confidence: 99%